Real‐world experience with mepolizumab: Does it deliver what it has promised?. Issue 6 (14th April 2020) - Schleich, Florence; Graff, Sophie; Nekoee, Haleh; Moermans, Catherine; Henket, Monique; Sanchez, Carole; Paulus, Virginie; Guissard, Françoise; Donneau, Anne‐Françoise; Louis, Renaud
Abstract: Background: Randomized control trials performed in selected populations of severe eosinophilic asthmatics have shown that mepolizumab, an anti‐IL5 therapy, was able to reduce exacerbations and OCS maintenance dose and in some studies, to improve asthma control and lung function. Objective: The aim of this study was to confirm the results of the RCTs in real‐life in a population of 116 severe eosinophilic asthmatics treated with mepolizumab and who were followed up at the asthma clinic every month for at least 18 months. Severe asthmatics underwent FENO, lung function, asthma control and quality of life questionnaires, sputum induction and gave a blood sample at baseline, after 6 months and then every year. Results: We found a significant reduction in exacerbations by 85% after 6 months ( P < .0001), which was maintained over time. We also found a significant and maintained reduction by 50% in the dose of oral corticosteroids ( P < .001). Patients improved their ACT (+5.31pts, p<0.0001) ACQ (‐1.13pts, P < .0001) and their AQLQ score (+1.24, P < .0001) at 6 months and this was maintained during follow‐up. Only 37% reached asthma control (ACQ <1.5, ACT> 20). We observed a progressive increase in post‐BD FEV1 that reached significance after 18 months (190ml or 11%, P < .01). Patients improving their FEV1had higher baseline sputum eosinophils than those not improving airway caliber. We found a significant reduction in sputum eosinophil counts by 60% after 6 months ( P < .01) and a maintained reduction in blood eosinophil counts by 98% ( P < .0001). Conclusion: In our real‐life study, we confirm the results published in the RCTs showing a sharp reduction in exacerbation and oral corticosteroids dose and an improvement in asthma control and quality of life. Clinical relevance: Mepolizumab is efficient in severe eosinophilic asthma in real life.